2016
DOI: 10.4314/sajas.v45i5.2
|View full text |Cite
|
Sign up to set email alerts
|

A balanced perspective on animal welfare for improved meat and meat products

Abstract: Increased public concern for animal welfare in the logistics chain has led to a rise in the scrutiny of the treatment of food animals. Factors affecting the status of welfare of slaughter animals begin at the farm and occur during transportation and at the abattoir. The activities that animals pass through before slaughter are thought to have negative effects on both the animal and the product. Before or during this period, animals suffer pain, which compromises their physical, health and biochemical status, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 161 publications
0
16
0
2
Order By: Relevance
“…Likewise, the frequency of carcasses with skin lesions and the prevalence of DFD meat increased progressively with longer lairage . Adverse weather conditions have an impact on ante-and post-mortem muscle glycogen stores, which leads to higher incidences of bruised carcasses and DFD meat in winter, while animal losses and the risk of PSE meat increase in summer (Guárdia et al, 2004, Guárdia et al, 2005, Chulayo & Muchenje, 2015. Several studies showed that an increase in the slaughter weight of fattening pigs diminishes carcass and meat quality characteristics (Cisneros et al, 1996, Latorre et al, 2004, Czyżak-Runowska et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the frequency of carcasses with skin lesions and the prevalence of DFD meat increased progressively with longer lairage . Adverse weather conditions have an impact on ante-and post-mortem muscle glycogen stores, which leads to higher incidences of bruised carcasses and DFD meat in winter, while animal losses and the risk of PSE meat increase in summer (Guárdia et al, 2004, Guárdia et al, 2005, Chulayo & Muchenje, 2015. Several studies showed that an increase in the slaughter weight of fattening pigs diminishes carcass and meat quality characteristics (Cisneros et al, 1996, Latorre et al, 2004, Czyżak-Runowska et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of slaughter animals from the farm habitat exposes them to various unfamiliar conditions and handling methods at all stages from the farm to the knocking box at the abattoir (Ferguson & Warner, 2008). Therefore, there is need to pay attention to animal welfare in all stages of production, in order to improve product quality (Chulayo & Muchenje, 2015). Steer transportation has been described as the key component joining the events involved in the preslaughter logistics chain (Miranda-de la Lama et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increasing consumer scrutiny of the conditions production animals are reared in, particularly regarding their wellbeing and health, producers ought to comply. Chulayo and Muchenje [54] reported that AW is generally associated with producers, retailers and the industry, with no consumer consideration, though it may affect their attitudes towards and purchase decision of certain products. Hence, the current status re garding awareness of AW matters disqualifies the region from import and export participation with the rest of the world, as reflected in a sluggish contribution towards economic growth [14,15,47,55].…”
Section: Animal Welfare In African Conditionsmentioning
confidence: 99%